Pengaruh Gaya Hidup Dan Kelompok Referensi Terhadap Keputusan Pembelian Laptop Asus Dan Acer (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Kevin Johan Delaris Putra; Nur Hidayati; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the influence of lifestyle and reference groups on the purchase decision of Asus and Acer brand laptops. This type of research is quantitative research. The sampling technique was obtained using the purposive sampling method with the number of samples obtained as many as 70 respondents who were students of the Faculty of Economics and Business, Islamic University of Malang who used Asus and Acer laptops. The data analysis used in this study used validity and reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heterokedasticity tests, t tests and R2 coefficients of determination. The results of this study show that style has a positive and significant effect on the purchase decision of Asus and Acer laptops and the reference group has a positive and significant effect on the purchase decision of Asus and Acer laptops. Keywords : Lifestyle, Reference Groups Purchasing Decision.